1998
DOI: 10.1139/t97-087
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and softening behaviour of La Biche shale

Abstract: Free swell, semiconfined swell, and one-dimensional oedometer swell tests were performed on La Biche shale specimens in solutions of different salinities. The swelling behaviour of La Biche shale was found to be highly anisotropic and dependent on electrolyte concentration, stress, and swelling history. Drained triaxial compression tests were conducted on La Biche shale specimens subjected to different degrees of swelling. The test results indicate that the Young's modulus decreases with increasing swelling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 7 publications
0
37
0
1
Order By: Relevance
“…The disjoining pressure is thus a microscopic concept which must be analyzed at the pore scale. The macroscopic swelling pressure which can be measured in natural materials [see, e.g., Madsen and Vonmoos, 1985;Huang et al, 1986;Wong, 1998] is associated with the wellknown swelling properties of certain clays (e.g., smectite). This pressure is currently described as the external stress that has to be applied to a clay-rock sample in order to maintain its mechanical equilibrium (prevent swelling).…”
Section: Introductionmentioning
confidence: 99%
“…The disjoining pressure is thus a microscopic concept which must be analyzed at the pore scale. The macroscopic swelling pressure which can be measured in natural materials [see, e.g., Madsen and Vonmoos, 1985;Huang et al, 1986;Wong, 1998] is associated with the wellknown swelling properties of certain clays (e.g., smectite). This pressure is currently described as the external stress that has to be applied to a clay-rock sample in order to maintain its mechanical equilibrium (prevent swelling).…”
Section: Introductionmentioning
confidence: 99%
“…He also investigated the effect of swelling under different salt concentrations of the water added in swelling tests. (b) swollen specimens at a confining stress of 50 kPa (after Wong, 1998) stress, a profound degradation in strength and stiffness is observed in the subsequent triaxial test (Fig. 7(b)).…”
Section: Drying-wetting Cyclesmentioning
confidence: 97%
“…The behaviour of La Biche shale (Wong, 1998) The particular triaxial tests reproduced in Fig. 7(b) were selected for the comparison exercise.…”
Section: Modelling Some Reported Experimentsmentioning
confidence: 99%
“…Al-Mhaidib and Al-Shamrani [10] reported that the shear strength of the expansive shale and bentonite, obtained from triaxial testing, decreased by 70% to 90% because of a full swelling. Wong [11] investigated the effect of both swelling and confining stress on the shear strength of an expansive shale, and found that the shear strength of the tested shale decreased with increasing swelling. Zhang et al [12] discussed the impact of wet-dry cycles with loading on the expansive soil strength but did not give specific values for shear strength parameters.…”
Section: Introductionmentioning
confidence: 99%